Describing researchers’ ways of seeing a lesson: As the first work of the cross-cultural study on lesson study between Japan and Thailand Décrire la manière dont les chercheurs voient une leçon: premier travail de l’étude interculturelle sur l’étude des leçons entre le Japon et la Thaïlande - Mizoguchi, Tatsuya; Inprasitha, Maitree; Changsri, Narumon; Shinno, Yusuke (Educação Matemática Pesquisa Revista do Programa de Estudos Pós-Graduados em Educação Matemática, 2020)
Abstract This research is the first work of the project of cross-cultural study on lesson study between Japan and Thailand. Lesson study is currently an international topic, and we use “lesson study” as a common word. However, are the meanings of each terminology in diverse languages as same completely? Our initial concern is in this point. For this, we observe lesson on video and make comment-reports on it in each. In analyzing these comments, it is required a meta theory for descriptions. In this research, we describe the researchers ways of seeing a lesson using the Anthropological Theory of the Didactic [ATD or TAD in French and Spanish]. In conclusion, we discuss similarities and discrepancies between researchers’ comments of both countries in terms of a) praxis and logos blocks, b) mathematical and didactic organization, and c) the perspective of scale of levels of didactic co-determinacy [LDC]. Keywords: Lesson study; Cross-cultural study; Japan and Thailand Résumé Cette recherche est le premier travail du projet d’étude interculturelle sur l’étude de la leçon entre le Japon et la Thaïlande. L’étude de la leçon est actuellement un sujet international, et nous utilisons la « lesson study » comme un mot commun. Cependant, les significations de chaque terminologie dans diverses langues sont-elles identiques? Notre préoccupation initiale concerne ce point. Pour cela, nous observons une leçon sur la vidéo et faisons des commentaires sur chacune d’elles. En analysant ces commentaires, il faut une méta-théorie pour les descriptions. Dans cette recherche, nous décrivons les chercheurs pour voir une leçon en utilisant TAD. En conclusion, nous discutons des similitudes et des divergences entre les commentaires des chercheurs des deux pays en termes de blocs de praxis et logos, b) l’organisation mathématique et didactique, et c) la perspective des niveaux de la codétermination didactique. Mots-clés: Étude de cours, Étude interculturelle, Japon et Thaïlande